Changing Disease profile of medical inpatients on the first post admission day of a Tertiary Care hospital (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Population demography of the world including Bangladesh is on transition. The increasing number of elderly persons has a direct impact on the demand for health services due to the consequent rise in degenerative diseases of aging and changing life style.Objective: The objective was to know the disease pattern of the geriatric group of medical inpatients on the first post admission day.Methodology: This was a cross sectional observational study. It was conducted in the wards of Medicine department of Dhaka Medical College Hospital from the 1st of March to 15th March, 2016.Results: Total 552 patients admitted in the study period. Of them 286 patients were male (51.8%) and 266 were female (48.2%). 176 patients (31.88%) were over the age of 60 years. Median age of the admitted patients is 44.5 years. In geriatric age group regardless of primary diagnosis 78(44.32%) patients had diabetes, 103(58.52%) cases were hypertensive; 31(17.61%) cases were ischemic heart diseases; 26(14.77%) cases were chronic kidney disease, 24(13.64%) cases were presented with stroke; another 24(13.64%) cases were suffering from COPD.Conclusion: In conclusion most common geriatric diseases are diabetes mellitus, hypertension, ischaemic heart disease, and chronic kidney disease.Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 113-115